Al-Mash'ar Al-Haram in the Holy Qur’an: A Maqasid-Based Exegetical Study in Light of Qur’anic Context (Abhat Journal, 2025)
This study presents a maqasid-oriented exegetical analysis of Al-Mash'ar Al-Haram as mentioned in the Qur’an, focusing on the interpretation of related verses within their Qur’anic context and in light of the higher objectives of Islamic law. The research aims to explore the semantic and spiritual dimensions of this sacred site as well as to examine the Prophet Muhammad’s ﷺ actions there, and derive relevant jurisprudential rulings. It also investigates the influence of modern innovations, particularly artificial intelligence, on the organization of sacred rituals and the fulfillment of Hajj objectives. The significance of the study lies in its engagement with a central element of pilgrimage, offering a deeper understanding of Qur’anic texts through a contemporary lens. The topic was chosen to bridge classical tafsir with present-day developments, especially in the management of sacred spaces.The researcher adopts analytical, inductive, and maqasid-based methodologies, incorporating a civilizational perspective to assess how technological advancements contribute to the realization of spiritual and logistical goals in Hajj.The findings suggest that recent innovations have enhanced crowd management and that artificial intelligence plays an important role in Hajj.
Keywords: Al-Mash'ar Al-Haram; Muzdalifah; Arafah; remembrance of Allah